Impacts of urban safety net on income, food expenditure and intake capacity of poor households in Addis Ababa city, Ethiopia, 2021 - Tareke, Kassa Moges (Frontiers in Sustainable Food Systems, 2022)
Although measures taken to address food insecurity and income inequality showed notable outcomes, they have continued to be major global issues mainly in urban areas of developing countries. To relieve these problems, Ethiopia started an urban safety net program in Addis Ababa city in 2017. The purpose of this study was to investigate the impacts and progress of the urban safety net program, mainly its cash transfers (CTs) on income, consumption, and food security of poor households using indicators based on elements of a theory of change and Engel's coefficient. It assessed whether the program was significant (or not) to program beneficiaries compared to situations before the start of the program, non-beneficiaries, and beneficiaries' sex. A total of 560 sample households were selected through a multi-stage sampling for household surveys. Comparative approaches, paired and independent t-tests, and linear regression were used to analyze the data. Results revealed that the CTs had a satisfactory targeting accuracy of the poor and produced positive effects on monthly income, savings, food expenditures and intake, and seed money for a business start. Since financial transfers account for a larger proportion of the income of households, current income becomes significantly bigger compared to income during the pre-program periods and non-beneficiary households. Food access, expenditure, and savings capacities of beneficiaries in post-CT became better than in pre-CT along with better food access and diet intake two to three a day than non-beneficiaries. Besides, coverage and benefits were statistically significant for women compared to men. The implementation of the urban safety net program is good in its positive impacts and progress toward nutrition and food security of poor households as a result of an increase in their income, food expenditure, intake, and access. This implies policymakers could potentially expect to see improvements in nutrition and food security, especially when targeting urban poor and female-headed households. However, delays in payments and work equipment, declining size and value of payments, and weak supplementary services are the program's shortcomings. Policy implications to improve the size of transfers, emergency aids, timely payments and equipment provisions, and interventions like regular business training, supervision, and guidance are recommended.